Wide‐angle beam‐scanning transmitarray antenna with low scan loss. Issue 2 (11th November 2022) - Song, Wenke; Ding, Haibing; Cai, Yang; Guo, Naining; Liu, Kegang; Li, Sen; Wang, Jing; Wang, Han; Xue, Qianzhong
Abstract: In this letter, a mechanical beam‐scanning transmitarray antenna with a wide scan coverage is presented. A wide‐band element is designed to provide a linear transmission phase shift with a low transmission loss, which comprises a double‐arrow and two orthogonal grid polarizers printed on two substrates. Then, a dual‐beam phase matching method is introduced to reduce the scan loss. To verify the design, a 437‐element transmitarray with a circular aperture ( D = 150 mm) is simulated, fabricated, and measured. The measured results indicate that the transmitarray antenna achieves a ±40° scan coverage while keeping a low scan loss (<1.8 dB). The side lobe levels keep lower than −15 dB in the entire scanning range. Moreover, a 1‐dB gain bandwidth of 21% (14–17.2 GHz) can be achieved in terms of boresight radiation, and the measured peak gain is 23.5 dBi at 15 GHz.